Management of patients with forearm and hand injuries - Bisht, Bhaskar; Rajan, Manu; Dvivedi, Sanjay; Rawat, Kinnari A. V.; Konda, Sireesha (International Surgery Journal, 2020)
Background: Injuries to the hand and the forearm, particularly crush injuries have always been a major challenge to even the best of surgeons, whether it is a major case of a mangled hand by a high pressure injury or even a small case as an injury to the tip of the finger by getting squashed in a closing door. Any injuries in the forearm and the hand requires a very meticulous and thoughtful approach towards coverage with the aim of maximal restoration of function as well aesthetic appearance. Methods: The study was conducted in the Department of Surgery, Himalayan Institute of Medical Sciences (HIMS), Swami Ram Nagar, Dehradun, over the period of 12 months. Subjects were recruited from patients presenting in emergency/surgery OPD, HIMS, Dehradun with a primary diagnosis of soft tissue injuries in the forearm and the hand. A total of 114 patients were included in the study. Results: 39.5% (45 patients) were treated with combined modalities, including debridement, grafting & flap coverage. 14.1% (16 patients) required some form of orthopaedics intervention. 21.1% (24 patients) needed neurovascular or tendon repair surgery. 37.7% (43 patients) faced some sort of early or late complications. Conclusions: Proper assessment and management of complex injuries of hand and forearm is mandatory for a good functional and aesthetic outcome.